Split-week Programming for Secondary Physical Education: Inducing Behavioral Change for Lifetime Fitness. - Ferkel, Rick; Allen, Ray; True, Larissa; Hulteen, Ryan (JOPERD: The Journal of Physical Education, Recreation & Dance, 2018)
There is an imperative need for secondary physical education programming to prepare students for lifetime fitness and health. Physical activity levels in adolescents and adults are dismal, and the negative health outcomes associated with sedentary behaviors are catastrophic. Secondary physical education programs have the opportunity to implement a curriculum that can enable students to create and execute their own health-enhancing fitness plan. The current focus in most programs is on a sport and game model that has had limited results in influencing the adoption of healthy lifestyle habits. The purpose of this article is to provide practitioners with a practical and feasible split-week program model that is designed to potentially induce behavioral change in students for lifelong physical activity and fitness. The split-week program holds health-related fitness education at the core while also teaching outdoor recreation, sport and rhythmic activities.